Marks grading system for secondary school - Kundang, Gudin; Chai, Hong Lan; Mariam Jamilah, Abdullah; Aminah, Jamain (Universiti Malaysia Sarawak, UNIMAS, 2002)
This project involves developing a prototype of the Mark Grading System for Secondary School. Its main goal is to replace the current existing manual system of monitoring the performance of the students at SMK Semera, Asa Jaya, Kota Samarahan. Information that we gathered through observations and interviews during our Practicum in that school has revealed the weaknesses of the current manual system.